Handbook of Research on Social Marketing and Its Influence on Animal Origin Food Product Consumption - Bogueva, D.; Marinova, Dora; Raphaely, T. (IGI Global, 2018)
The Handbook of Research on Social Marketing and Its Influence on Animal Origin Food Product Consumption is a critical scholarly resource that examines the role of social marketing in understanding and changing behavior regarding the ...